PENINGKATAN KETERAMPILAN MENULIS NARASI MENGGUNAKAN MODEL CIRC PADA PESERTA DIDIK KELAS IX D SMP NEGERI 7 PATI SEMESTER GASAL TAHUN PELAJARAN 2017/2018 - Ihwan (Pusat Studi Pendidikan dan Kreativitas Guru, 2018)
One of the four language skills that must be mastered by students is writing skills. But in fact the skills of these students are still low. The results of the assessment of learning writing skills, especially writing the narrative text is still low, less than KKM that has been set at 75. This study aims to find out how is the implementation of learning with CIRC model to improve the skills of writing narrative in IX D SMP Negeri 7 Pati Odd Semester Year 2017/2018 and to find out whether the skills of writing the narrative of class IX D SMP 7 Pati Odd Semester Year 2017/2018 can be improved through learning by CIRC model. This research is a classroom action research designed with 2 cycles. The results showed that after the implementation of the second cycle. It was increased to 78. The value of learning implementation is 87. Based on research results analysis, it was concluded that the implementation of learning with CIRC model to improve the skills of writing narrative in IX D SMP Negeri 7 Pati Odd Semester Year 2017/2018 goes well and the skills of writing the narrative of IX SMP Negeri 7 Pati in Odd Semester Year 2017/2018 can be improved through learning with CIRC model.